2023
DOI: 10.1111/dom.15233
|View full text |Cite
|
Sign up to set email alerts
|

Remnant cholesterol, but not low‐density lipoprotein cholesterol, is associated with intra‐pancreatic fat deposition

Loren Skudder‐Hill,
Ivana R. Sequeira‐Bisson,
Juyeon Ko
et al.

Abstract: AimTo investigate the associations of components of the lipid panel (and its derivatives) with intra‐pancreatic fat deposition (IPFD).MethodsAll participants underwent abdominal magnetic resonance imaging on the same 3.0‐Tesla scanner and IPFD was quantified. Blood samples were collected in the fasted state for analysis of lipid panel components. A series of linear regression analyses was conducted, adjusting for age, sex, ethnicity, body mass index, fasting plasma glucose, homeostatic model assessment of insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This cross-sectional study was part of the COSMOS programme 20 and approved by the Health and Disability Ethics Committee of New Zealand (13/STH/182). Residents of Auckland (New Zealand) were eligible to participate in the study if they were at least 18 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study was part of the COSMOS programme 20 and approved by the Health and Disability Ethics Committee of New Zealand (13/STH/182). Residents of Auckland (New Zealand) were eligible to participate in the study if they were at least 18 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…A randomised controlled trial of a diet characterised by whole grains, legumes, and fruits and vegetables, compared with a diet high in refined grains, found that increased intake of dietary fibre leads to higher levels of circulating bile acids in healthy adults [48]. Since cholesterol is the precursor of bile acids, binding with dietary fibre results in increased excretion of bile acids in the form of bile salts [10,49]. As a result, the liver is required to synthesise bile acids using endogenous cholesterol, reducing serum cholesterol levels.…”
Section: Effect On Lipid Metabolismmentioning
confidence: 99%
“…While it remains to be established conclusively that sustained low-grade inflammation after AP induces novel insulin resistance, recent findings from the longitudinal LACERTA cohort study do indicate that fasting insulin is a significant risk factor for new-onset derangements in glucose metabolism following an attack of AP [122]. Other key factors involved in the pathogenesis of PPDM include intra-pancreatic fat deposition, altered lipid metabolism, and dysfunction of the pancreasgut-brain axis [49,123,124]. Detailed recommendations on the differential diagnosis of PPDM and type 2 diabetes have been published elsewhere [115].…”
Section: Pancreatitis and Post-pancreatitis Diabetes Mellitusmentioning
confidence: 99%